(untitled) (Jurnal Matematika, Statistika dan Komputasi, 2025)
The Spatial Autoregressive Moving Average (SARMA) model is a regression model developed from the classical regression model. The classical regression model produces inaccurate conclusions when used to model spatial data because the assumption of independent errors is not met. The SARMA model has advantages in modeling spatial data that has a spatial effect on the lag of the dependent variable and error. This study aims to obtain a SARMA model and factors that significantly influence the Human Development Index (HDI) of districts and cities in Kalimantan in 2022 based on the SARMA model. The spatial weighting used in SARMA modeling is rook contiguity. The results of the study show that the SARMA model can model the HDI of districts and cities in Kalimantan. The factors that significantly influence the HDI of districts and cities in Kalimantan are the poverty rate, the open unemployment rate, and the number of hospital facilities.